Geistige Gefahr und Immunisierung der Gesellschaft. Antikommunismus und politische Kultur in der frühen Bundesrepublik - Creuzberger, Stefan (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte Sondernummer, 2014)
Up to the early 1960s, anticommunism was an important source of identity formation in the Bonn Republic. It aimed at consolidating the still-nascent West German democracy. Renowned historians discuss different governmental and social forms of anticommunism in the pan-German context.